2019
DOI: 10.1080/2090598x.2019.1647676
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral disease and intratesticular haemodynamics as markers of dyspermia in patients with subclinical varicocele: A prospective study

Abstract: Objective: To study scrotal ultrasonographic characteristics in patients with subclinical varicocele (SV) and investigate their relationship with semen parameters.Patients and methods: In all, 56 men with SV were recruited and divided into two groups, according to their semen characteristics. Group A, comprised 34 men with normal semen analysis; and Group B, comprised 22 men who carried at least one abnormality, regarding sperm concentration, motility and morphology. Between the two groups we compared: age; bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Also, we examined the role of vein diameter on both sides and there was no significant difference between the groups. These results are in accordance with our previous study where no association was found between maximal vein diameter in men with SV and dyspermia (12). This does not sound surprising, as even in clinical forms, even grade seems to be inferior to reflux in terms of prediction of the results of varicocelectomy (25).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, we examined the role of vein diameter on both sides and there was no significant difference between the groups. These results are in accordance with our previous study where no association was found between maximal vein diameter in men with SV and dyspermia (12). This does not sound surprising, as even in clinical forms, even grade seems to be inferior to reflux in terms of prediction of the results of varicocelectomy (25).…”
Section: Discussionsupporting
confidence: 93%
“…In young boys, pattern of grade I reflux helps stratify the risk for hypotrophy and assist the follow-up (27). In our previous study in adult men, the pattern of the reflux (lasting all the duration of the Valsava vs short-lasting reflux) had not been linked to dyspermia in adults patients with subclinical varicocele (12). Reflux is note- worthy though, and the shunt-type (continuous) reflux is strongly associated with testicular hypotrophy in adolescents (28), whereas prolonged reflux may also predict the outcome of varicocelectomy in adults (25).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation